Internet of things time saving and management system for bus passengers - Ali Abdulaziz Alawad; Muhammad Tajammal Chughtai; Majid Faleh Alanzi (Institute of Advanced Engineering and Science, 2023)
This article presents a novel type of mobile phone application approach using the wireless fidelity (WiFi) system. Which is capable of facilitating the public transport user and its drivers efficiently. The application support passengers when there are scenarios where commuters face problems while using public transport. If users get bus information beforehand, such as bus location and arrival time, the number of passengers in the public transportation system. This application has been developed for the Android operating system. The application includes bus details like real-time bus location, bus arrival time, bus routes, bus stops, bus numbers, and so on. After the trip is booked, users' devices allow real-time geolocation to be shared in the application, helping the bus driver decide to stop at one stop or move to another when there are no users.